2004
DOI: 10.1242/jcs.01407
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress induces profound remodelling of keratin filaments and cell junctions inepidermolysis bullosa simplexkeratinocytes

Abstract: IntroductionAs the flexible outer covering of the body, the properties of skin must accommodate continuous stretching forces. The skin must be strong enough to endure physical trauma yet be flexible enough to allow a large range of movement. A large contribution to the physical resilience of epidermal skin cells comes from the keratin intermediate filaments that they express, as was shown with the discoveries that the inherited skin fragility disorder epidermolysis bullosa simplex (EBS) is caused by mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 33 publications
11
78
2
Order By: Relevance
“…When the intermediate filaments are disrupted, as in the human genetic disease epidermolysis bullosa and transgenic mice that mimic it, the epidermis is greatly weakened (Fuchs, 1996;Lane and McLean, 2004). Weakening or disrupting the interaction between desmosomes and intermediate filaments also diminishes the strength of epithelia (Huen et al, 2002;Russell et al, 2004). Scaffolding, like a chain, is only as strong as its weakest link.…”
Section: Discussionmentioning
confidence: 99%
“…When the intermediate filaments are disrupted, as in the human genetic disease epidermolysis bullosa and transgenic mice that mimic it, the epidermis is greatly weakened (Fuchs, 1996;Lane and McLean, 2004). Weakening or disrupting the interaction between desmosomes and intermediate filaments also diminishes the strength of epithelia (Huen et al, 2002;Russell et al, 2004). Scaffolding, like a chain, is only as strong as its weakest link.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, even mutations causing severe disease do not prevent formation of long keratin intermediate filaments (KIFs) in vitro (Herrmann et al 2002), suggesting that mutations and physical stress act at the level of keratin bundling, network organization, dynamics, or by affecting association with other proteins. Indeed, the most frequent KRT14 Arg125 mutation compromises desmosome adhesion (Russell et al 2004;Homberg et al 2015).…”
Section: Human Disease and Mouse Modelsmentioning
confidence: 99%
“…The resulting perinuclear keratin reorganization affects the viscoelasticity of metastatic cancer cells and promotes tumor invasion (Beil et al 2003). Mechanically stretching of keratinocytes expressing EBS-like keratin mutations triggered a progressive disassembly of desmosomes and weakened intercellular adhesion (Russell et al 2004;Homberg et al 2015). Thus, keratin reorganization on posttranslational modifications might contribute to the invasive properties of metastatic tumor cells and to altered adhesion in skin disorders (Beil et al 2003;Russell et al 2004;Homberg et al 2015;Loschke et al 2016).…”
Section: Impact Of Mechanical Stretch On the Desmosome -Keratin Complexmentioning
confidence: 99%
“…Studies in both stressed cells and cells expressing keratin mutants, have shown that altered keratin IF network dynamics and keratin reorganisation are accompanied by an elevation in keratin phosphorylation Russell et al, 2004;Werner et al, 2004). Since the association of 16E1^E4 with keratin results in altered keratin dynamics, we investigated the phosphorylation status of this malfunctioning 16E1^E4-associated keratin network.…”
Section: Cells Respond To 16e1^e4-induced Inhibition Of Keratin If Nementioning
confidence: 99%